1997
DOI: 10.1093/emboj/16.3.555
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferase activity and interaction with ADA2 are critical for GCN5 function invivo

Abstract: Yeast GCN5 is one component of a putative adaptor complex that includes ADA2 and ADA3 and functionally connects DNA-bound transcriptional activators with general transcription factors. GCN5 possesses histone acetyltransferase (HAT) activity, conceptually linking transcriptional activation with enzymatic modification at chromatin. We have identified the minimal catalytic domain within GCN5 necessary to confer HAT activity and have shown that in vivo activity of GCN5 requires this domain. However, complementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
165
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(175 citation statements)
references
References 67 publications
9
165
0
1
Order By: Relevance
“…Previous studies demonstrated that fusion of GCN5 to the bacterial LexA DNA-binding domain activated transcription in yeast. It was suggested that this activity was attributable to the HAT and ADA2 binding domains of GCN5 (44). In line with the previous studies, transfection of pBIND-GCN5 into 293T or U2OS cells activated the pG5luc luciferase reporter in a GCN5-dependent manner (Fig.…”
Section: B23 In Gcn5-dependent Histone Acetylation and Transactivationsupporting
confidence: 86%
“…Previous studies demonstrated that fusion of GCN5 to the bacterial LexA DNA-binding domain activated transcription in yeast. It was suggested that this activity was attributable to the HAT and ADA2 binding domains of GCN5 (44). In line with the previous studies, transfection of pBIND-GCN5 into 293T or U2OS cells activated the pG5luc luciferase reporter in a GCN5-dependent manner (Fig.…”
Section: B23 In Gcn5-dependent Histone Acetylation and Transactivationsupporting
confidence: 86%
“…Purified ADA and SAGA complexes both have been shown to contain the non-DNA-binding, transcriptional adaptor proteins Ada2p and Ada3p (8 -10). Consistent with these in vitro results, genetic experiments in yeast have documented that mutations in Ada2p or Ada3p yield phenotypes identical to loss of Gcn5p in terms of both transcriptional regulation at specific gene loci (11,12) and cell growth (11,13). In addition, several specific proteins have recently been identified as unique components of ADA or SAGA.…”
mentioning
confidence: 53%
“…The catalytic domain of the Gcn5 HAT is required for coactivator function in vivo, providing a genetic link between histone modification and transcriptional activation (23). As a human GCN5 homolog has been identified, this HAT is likely to be widely conserved (24,25).…”
Section: Tetrahymena Histone Acetyltransferase a And Yeast Gcn5mentioning
confidence: 99%
“…However, unlike the native HAT A enzyme, recombinant Gcn5 cannot acetylate nucleosomal histones, implying that other subunits in the complex must influence its activity on chromatin. Genetic and biochemical studies reveal at least two interacting proteins, Ada2 and Ada3, that form a complex with Gcn5 (23,(27)(28)(29). Binding of Ada2 to the activation domains of the transcriptional activators VP16 and Gcn4 in vitro suggests a mechanism by which promoter targeting of Gcn5 might be achieved (30,31).…”
Section: Tetrahymena Histone Acetyltransferase a And Yeast Gcn5mentioning
confidence: 99%